Danmarks fjerde krone. Dronning Louises brudekrone 1743 - Hein, Jørgen (Historisk Tidsskrift, 2019)
Denmark’s fourth crown. The nuptial crown of Queen Louisa from 1743 In the Royal Danish Collection at Rosenborg Castle is a small crown of gilt silver with a cap of crimson velvet and remnants of ermine trimming (figs. 2, 19). It is shaped like an English coronet consisting of a circlet with eight points, four crosses patées alternating with two fleurs-de-lys and two strawberry leaves, a combination used on the coronets of the children of the Heir Apparent in Britain today (fig. 3). The crown at Rosenborg can be traced back to an inventory from 1785, and it was thus believed to have been brought to Denmark by one of the two British princesses who became Danish queen during the eighteenth century: Caroline Mathilda, who married Christian VII in 1766 (fig. 4), or Louisa, who married Frederik V in 1743 (fig. 5). This guess must, however, be rejected. Evidence comes in the form of two silver gilt toilet sets that formed part of the brides’ trousseaus. On Caroline Mathilda’s toilet set, which was a gift from her brother George III, we find the monogram C(aroline) R(egina) under a ‘Continental’ crown with four intersecting arches (fig. 6). Likewise, the toilet set of Louisa is adorned with her initials under a coronet with alternating crosses patées and fleurs-de-lys conforming to a warrant that was issued by her father George II on his coronation in 1727 (figs. 7–8). If this be so, how can the different combination of points on the small crown at Rosenborg be explained? The answer is found partly in some hitherto unpublished invoices in the Danish privy purse, and partly in several descriptions of Louisa and Crown Prince Frederik’s entry into Copenhagen and subsequent wedding, in 1743. The day after their arrival at Frederiksberg Palace on the outskirts of the capital, Louisa met her parents-in-law, Christian VI and Sophie Magdalene, for the first time. Apparently, Louisa did not bring a coronet, and Queen Sophie Magdalene immediately ordered the present crown and an ermine robe to be made for the wedding ceremony four days later. The crown was made by goldsmith Hans Mundtberg, ‘working night and day’ and delivered on the day before the wedding in which it served as a nuptial crown for Louisa, who also wore the ermine robe. In ordering crown and robe for her daughter-in-law, Sophie Magdalene acted in perfect unison with Christian VI, who paid for both items. In close cooperation, the royal couple became the most prolific builders in Danish history, thus modernizing the state apparatus / framework of Danish absolutism. Both, however, lacked the ability to socialize and therefore avoided public representation, which made their subjects complain of an empty shell of pomp and circumstance. In 1743 the task of representation was left to the extrovert and popular crown prince and his charming wife. Their entry and wedding was staged with unprecedented splendour and magnificence that was carefully planned to include every rank of society (figs. 10–16). The ordering of the crown also raises the question of whether the use of nuptial crowns was a custom at the Danish court. A survey of the sparse and scattered sources indicates that bridal crowns were the norm rather than the exception in the period 1634–1829. Thus a nuptial crown with two cross arches and threaded diamonds was made for Caroline Mathilda in 1766.